'A Tale of Two Programs': Interrogating 'open(closed)ness' and 'cultural diversity' through critical observations of two Japanese University English language programs. (24th October 2015) - Toh, Glenn
Japan is known to be a country that manicures its socio-cultural borders. In this article I will examine discourses regarding openness, closedness and cultural diversity in relation to policies and practices that draw heavily on mythologies of English language as an inroad to greater openness and diversity. To do this I will examine two English language programs at two different Japanese universities where I have worked as an English teacher. My analysis will be done within a larger backdrop of discourses, histories and epistemologies depicting: (1) Japan as a monolingual and monocultural nation where cultural diversity has been systemically and strategically resisted (Befu, 2001 ;Lee, 2006 ); (2) contestations over claims, meanings, renditions and suppressions of internationalization and cultural diversity in contemporary Japan; and (3) current practices surrounding English teaching, recent changes at policy level enabling content courses to be taught in English, and their implications for understandings of cultural diversity given the plurality of cultures and canons identifiable with English. Through critical observations of English as a Foreign Language and English as a Lingua Franca programs, I will demonstrate how different epistemological assumptions and ideological agendas behind the programs influence understandings, renditions and enactments of what I call open(closed)ness and cultural diversity. I will also observe how subtleties, inconsistences and incongruities related to such open(closed)ness can in turn exert a wash back effect on policy decisions.